Ispitivanje opravdanosti i efikasnosti mehanizma međunaronog krivičnog pravosuđa / Examining the Justification and Effectiveness of International Criminal Justice Mechanisms - Mirković, Maja (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Parallel with the efforts to humanize war in the greatest extent possible, the ideas of an establishment of judicial bodies with mandate to determine criminal responsibility and punishment of persons for crimes committed during the war or in connection with the war have occurred, spanning for a few hundred years. After enormous suffering and senseless causalties in the World War II, the idea of obligations that go beyond the duty of obedience to national legislation was born. Horrifying images of most severe violations of international humanitarian law were ressurected on the territory of the former Yugoslavia and in Rwanda on the other side of the world. They caused direct reaction of the UN Security Council to exercise its powers as provided by the Chapter VII of the UN charter, which led to the establishment of the International Criminal Tribunal for the Former Yugoslavia and International Criminal Tribunal for Rwanda. Many international law experts saw this as last, best hope for a strong wave of atrocities that have marked too often both the international and internal armed conflicts. However, after only a decade of their work, serious objections and doubts about the operation and functioning of ad hoc tribunals have arisen, which range from the high costs of their maintenance to the small number of prosecutions and the long duration of proceedings. The purpose of this paper is to examine the justification and effectiveness of the ad hoc tribunals, as pioneer instruments of international criminal law.